RELATIONSHIP OF WHITE BLOOD CELL COUNTS, HAEMOGLOBIN AND ESR WITH IHD - Shahzad, Farhana; Tawwab, Shahzad; Abbas, Afia (Journal of Ayub Medical College Abbottabad, 2009)
Objectives: To find any association of white blood cells, haemoglobin and ESR with ischemic heart disease in high risk native population. Methodology: The study included 93 male patients with Ischemic heart disease, between 40 and 60 years of age; 96 age and gender matched subjects. All study participants were non-diabetics. Complete blood cells count, haemoglobin and ESR levels were compared between the patient and control groups. Results: Total leukocyte counts along with neutrophils were significantly higher in the test group compared to the control population (p<0.001) and lymphocytes were significantly lower (p<0.001) in the patient group as compared to the control group. Haemoglobin levels were significantly lower (p<0.001) and ESR was higher (p=0.030) in the patient group as compared to the control group. Conclusion: Although, our findings of the study variables extend previous reports, the prevalence and prognostic importance of theses variables in IHD should be assessed in future experimental studies. These parameters could be important in public health because they are routinely measured by clinicians and may be helpful to predict the risk of future and secondary ischemic events in a high risk population. Keywords: TLC, DLC, Haemoglobin, ESR, Ischemic Heart Disease